Structural Phase Transitions and Thermal Hysteresis in the Metal-Organic Framework Compound MIL-53 As Studied by Electron Spin Resonance Spectroscopy - Mendt, Matthias; Jee, Bettina; Stock, Norbert; Ahnfeldt, Tim; Hartmann, Martin; Himsl, Dieter; Poeppl, Andreas (Journal of Physical Chemistry C, 2010)
The dehydrated aluminum form of the metal organic framework compound MIL-53 shows a temperature-driven phase transition with pronounced structural hysteresis as recently shown by neutron diffraction and scattering experiments (Liu et al. J. Am. Chem. Soc. 2008, 130, 11813). Thereby, the structure of the corner-sharing metal AlO(4)(OH)(2) octahedra differs in terms of local symmetry for the dehydrated MIL-53(Al) material in its high- and low-temperature form with open or closed pore structure, respectively. In this work, some of the framework aluminum ions were exchanged by chromium(III) to introduce an electron spin resonance (ESR) active probe ion. The resulting material was investigated by means of ESR and electron nuclear double resonance (ENDOR) spectroscopy to verify the incorporation of chromium at the octahedral framework sites. In addition, variable-temperature ESR measurements were performed to analyze the temperature-dependent phase behavior of the doped MIL-53 material. The Cr(III) ions have an electron spin S = 3/2 which shows a characteristic fine structure interaction depending very sensitively on the local symmetry of the chromium site. Therefore, the fine structure splitting of the Cr(III) probe ions allows for a concise elucidation of changes in the local symmetry at the CrO(4)(OH)(2) octahedra which occur upon structural transitions. In agreement with results from neutron experiments, the transformation from the open to the closed pore structure was found to occur in the temperature range between 150 and 60 K whereas the back transformation is taking place within a smaller temperature interval between 330 and 375 K.